2019
DOI: 10.5483/bmbrep.2019.52.6.140
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic influence on macrophage polarization and pathogenesis

Abstract: Macrophages play an essential role not only in mediating the first line of defense but also in maintaining tissue homeostasis. In response to extrinsic factors derived from a given tissue, macrophages activate different functional programs to produce polarized macrophage populations responsible for inducing inflammation against microbes, removing cellular debris, and tissue repair. However, accumulating evidence has revealed that macrophage polarization is pivotal in the pathophysiology of metabolic syndromes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 142 publications
(132 reference statements)
3
140
0
Order By: Relevance
“…Exposure of human monocytes to C. albicans , β-glucan and LPS triggers an increase in glycolysis, lactate secretion and ROS production [ 28 , 45 ]. Similarly, metabolic changes underpin polarization of macrophages, either to pro-inflammatory M1 or protective M2 [ 46 ]. M1 macrophages are highly glycolytic, have limited oxidative phosphorylation and increased flux via the pentose phosphate pathway, while M2 macrophages rely on the TCA cycle and oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of human monocytes to C. albicans , β-glucan and LPS triggers an increase in glycolysis, lactate secretion and ROS production [ 28 , 45 ]. Similarly, metabolic changes underpin polarization of macrophages, either to pro-inflammatory M1 or protective M2 [ 46 ]. M1 macrophages are highly glycolytic, have limited oxidative phosphorylation and increased flux via the pentose phosphate pathway, while M2 macrophages rely on the TCA cycle and oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors also found that etomoxir was able to inhibit M2 polarization in both control and Cpt2-deficient BMDM, which suggests that the data based on the use of etomoxir must be taken with caution, since it is possible that CPT1 has other functions outside FAO or that etomoxir is not specific for CPT1 (51). Divakaruni et al further supported this by showing that etomoxir has off-target effects indeed and that the inhibition of M2 polarization by this compound happens through the alteration of CoA levels rather than the inhibition of fatty acid oxidation (52). Overall, the available data suggest that the role of FAO in macrophage polarization is more complicated than initially thought.…”
Section: Dual Role Of Lipid Metabolism In Macrophage Polarizationmentioning
confidence: 99%
“…Besides LPS and leptin, other factors that are elevated in the obese condition, such as saturated fatty acids and glucose, have been discussed as capable of polarizing macrophages towards an inflammatory phenotype but will not be discussed in this review. Instead, the reader is directed to several comprehensive reviews on this topic [38,76,[119][120][121][122][123][124][125][126].…”
Section: Pancreatic Stromal Macrophages In the Obese Statementioning
confidence: 99%